The Role of the Constitution in Achieving Sustainable Development: A Reading in the Draft of the Libyan Constitution 2017 (Journal of human and social sciences, 2023)
In light of global developments across political, social, economic, and developmental dimensions, sustainable development has emerged as a vital pillar for advancing societies. The Draft Libyan Constitution of 2017 reflects this orientation, particularly in Article (22), which stipulates the state’s commitment to ensuring social justice, balanced and sustainable development through the rehabilitation of cities and villages, fair distribution of wealth, projects, and services, as well as providing equal job opportunities, encouraging investment, and addressing the needs of less-developed regions. Through an analysis of this article, the study highlights the state’s obligation to advance urban development and implement projects that serve the public interest, especially in light of the destruction and stagnation caused by the 2011 events, which damaged infrastructure, halted major projects, and suspended the activities of international construction companies—leading to the disruption of development and public services. The study concludes by emphasizing the importance of achieving developmental balance across regions, fostering projects that promote good governance, and advancing production methods and techniques. Sustainable development, it argues, rests on the integration of economic growth with the preservation of natural, environmental, and social resources, thereby ensuring a comprehensive approach to a sustainable future. Keywords: Constitution, Sustainable development, Social justice, Libya 2017.
Keywords: Libyan Constitution; Sustainable Development; Social Justice; Draft Constitution 2017; Balanced Development